Faktor-Faktor yang Mempengaruhi Struktur Modal pada Perusahaan Sektor Property dan Real Estate - Elsya Eryan; Siti Ruhana Dara (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this study is to analyze the effect of profitability, liquidity, growth and firm size on capital structure. The sample used in this study is property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. 41 companies were taken as samples. The sampling method used purposive sampling technique. The analysis uses the Fixed Effect Model in testing the hypothesis. The results of this study indicate that profitability has a negative effect on capital structure. Liquidity has a positive influence on the capital structure. Growth has no effect at all on capital structure and firm size has a positive effect on capital structure.